Distance Learning Delivery Modalities Implementation, Resilience Quotient, and Work Performance of Teachers: A Correlational Study in The Philippines - Reynald Joseph B. Fonte; Alberto D. Yazon; Consorcia S. Tan; Lerma P. Buenvinida; Marcial M. Bandoy (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
The study assessed the relationship between the dimensions of Distance Learning Delivery Modality (DLDM) implementation, resilience quotient, and work performance among public secondary teachers in the 5 City Schools Divisions in Laguna for the school year 2020-2021. Eight Hundred Fourteen (814) public school secondary teachers responded to the study. The global outbreak of COVID-19, a highly contagious coronavirus type, poses unprecedented challenges, particularly in education. Like everyone else, teachers face challenges that test their resilience. The researcher employed the descriptive-correlational research design and researcher-made questionnaire for the Level of DLDM implementation and work performance while an adopted questionnaire in measuring the teachers’ resilience quotient at work. Mean, standard deviation, Pearson r and Multiple Linear Regression Analysis were the statistical tools utilized to analyze and interpret the data gathered. Findings revealed that the teachers were implementing the DLDM properly, they were very resilient at work, and their work performance was very satisfactory. The teachers' level of DLDM implementation and resilience quotient affected the teachers' work performance. Four (4) domains of the teachers' resilience quotient, namely finding your calling, staying healthy, interacting cooperatively, and living authentically, and the design construct of the DLDM Implementation significantly predict the work performance of the teachers. School officials and administrators in the teacher training institute may design and conduct different training programs for the teachers that may enhance their level of resilience quotient and work performance in the new normal. Other elements that may predict teacher performance must be investigated in the future.